SOIL TRANSMITTED HELMINTHS EGGS CONTAMINATION IN CABBAGES (Brassica oleracea var. capitata) FROM PALEMBANG’S TRADITIONAL MARKETS - Daffa Rafid Yunanda; Dwi Prasasty, Gita; Susilawati; Dwi Handayani; Dalilah (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Indonesian people like to consume a number of raw vegetables, one of which is cabbage. Even though it has been washed clean, raw cabbage is still at risk of containing STH eggs and transmitting worms. This study aimed to determine STH egg contamination in raw cabbage, used a descriptive observational design with a cross-sectional approach. A total of 30 cabbage samples were taken randomly from 10 sellers at the traditional market. Samples were analyzed using the sedimentation method and STH eggs were identified under a microscope. All cabbage vegetables in the market were placed on the table, which indicates fairly good hygiene practices. However, one in 30 samples (3.33%) was contaminated with Ascaris lumbricoides eggs. These findings highlight the importance of improving vegetables hygiene and public awareness regarding cooked consumption.